2021
DOI: 10.3390/ijms222111926
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Charge Transfer of 1-Aminoanthraquinone and Ultrafast Solvation Dynamics of Dimethylsulfoxide

Abstract: The intramolecular charge transfer (ICT) of 1-aminoanthraquinone (AAQ) in the excited state strongly depends on its solvent properties, and the twisted geometry of its amino group has been recommended for the twisted ICT (TICT) state by recent theoretical works. We report the transient Raman spectra of AAQ in a dimethylsulfoxide (DMSO) solution by femtosecond stimulated Raman spectroscopy to provide clear experimental evidence for the TICT state of AAQ. The ultrafast (~110 fs) TICT dynamics of AAQ were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…S14 in the Supplementary Information, the ν C=C + ν 8a,sym and ν as,NO2 modes also show strong coherent oscillations in the center frequencies, where the similar frequencies of 79 and 146 cm −1 , respectively, were obtained as those from the population dynamics of both vibrational modes. Coherent oscillations in the excited-state vibrational results often represent that the reaction coordinates of the ICT of DNS are strongly coupled to the low-frequency vibrational modes, for example, out-of-plane deformation vibrations relevant to the structural changes of the chromophore in the specific excited-state processes 59 , 63 , 65 , 83 87 . Figure S15 in the Supplementary Information lists the out-of-plane deformation modes of DNS in the S 1 excited state with a planar geometry, which can be related to the twist of the nitrophenyl group upon the ICT in the excited state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S14 in the Supplementary Information, the ν C=C + ν 8a,sym and ν as,NO2 modes also show strong coherent oscillations in the center frequencies, where the similar frequencies of 79 and 146 cm −1 , respectively, were obtained as those from the population dynamics of both vibrational modes. Coherent oscillations in the excited-state vibrational results often represent that the reaction coordinates of the ICT of DNS are strongly coupled to the low-frequency vibrational modes, for example, out-of-plane deformation vibrations relevant to the structural changes of the chromophore in the specific excited-state processes 59 , 63 , 65 , 83 87 . Figure S15 in the Supplementary Information lists the out-of-plane deformation modes of DNS in the S 1 excited state with a planar geometry, which can be related to the twist of the nitrophenyl group upon the ICT in the excited state.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, FSRS with both high spectral (< 10 cm −1 ) and temporal (< 50 fs) resolutions was used to investigate the ultrafast structural dynamics of nitroaromatic push–pull chromophores during the ICT process in the excited state 57 59 . The FSRS has been successfully applied in the observation of various ultrafast dynamics in the excited states, including the intra- and inter-molecular proton transfers 60 63 , charge transfers 33 , 64 , 65 , etc 66 , 67 . The population dynamics and the peak shifts of the major vibrational modes in the finger-print frequency range would provide sufficient structural information of chromophores in the excited states.…”
Section: Introductionmentioning
confidence: 99%
“…From the kinetic analysis based on the biexponential functions, two fast time constants of 0.11 and 1.8 ps were retrieved for the vibrational Stokes shifts of DMSO. The instantaneous changes in the solvation shells, such as intermolecular hydrogen bonding between the solute and solvent molecules, have been reported in polar protic solvents [27,[52][53][54][55]. Scholes et al reported the inertial solvent responses of water and methanol in the ultrafast time scales of 40-150 fs in the light-harvesting proteins [54].…”
Section: Solvation Dynamics Of Dmsomentioning
confidence: 99%
“…Scholes et al reported the inertial solvent responses of water and methanol in the ultrafast time scales of 40-150 fs in the light-harvesting proteins [54]. The coherent oscillations in the vibrational modes of chromophores in protic and aprotic polar solvents have often been interpreted as the solvation dynamics of water or DMSO with the time constants of 190-250 fs, which is considered to facilitate the ultrafast proton and charge transfers in the excited states [27,55].…”
Section: Solvation Dynamics Of Dmsomentioning
confidence: 99%
See 1 more Smart Citation